Elucidating the Exceptional Passivation Effect of 0.8 nm Evaporated Aluminium on Transparent Copper Films - Bellchambers, Philip; Lee, Jaemin; Varagnolo, Silvia; Amari, Houari; Walker, Marc; Hatton, Ross A. (Frontiers in Materials, 2018)
Slab-like copper films with a thickness of 9 nm (~70 atoms) and sheet resistance of ≤ 9 Ω sq-1 are shown to exhibit remarkable long-term stability towards air-oxidation when passivated with an 0.8 nm aluminium layer deposited by simple thermal evaporation. The sheet resistance of 9 nm Cu films passivated in this way, and lithographically patterned with a dense array of ~6 million apertures per cm-2, increases by less than 3.5% after 7000 hrs exposure to ambient air. Using a combination of annular-dark field scanning transmission electron microscopy, nanoscale spatially resolved elemental analysis and atomic force microscopy, we show that this surprising effectiveness of this layer results from spontaneous segregation of the aluminium to grain boundaries in the copper film where it forms a ternary oxide plug at those sites in the metal film most vulnerable to oxidation. Crucially, the heterogeneous distribution of this passivating oxide layer combined with its very low thickness ensures that the underlying metal is not electrically isolated, and so this simple passivation step renders Cu films stable enough to compete with Ag as the base metal for transparent electrode applications in emerging optoelectronic devices.